Pendampingan Strategi Pemasaran secara Online pada Home Industry Rengginang di Desa Padaelo, Kajuara, Bone, Sulawesi Selatan - Suriyati, Suriyati; Putri, Francisca Tree Aulia; Irmayanti, Irmayanti (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The activity of implementing home industry assistance in online marketing aims to provide insight to home industry owners regarding online marketing strategies that are very important for increasing product sales. This activity uses the mentoring method. where this activity was carried out for about two months together, which then the author first prepared important equipment and infrastructure, such as rengginang labels and packaging, and carried out rengginang packaging with the rengginang home industry business owner, bearing in mind that the home industry did not yet have packaging for its products. Next, the author explains information related to online marketing strategies. Then the next step is to practice the process of creating a digital marketing account with the rengginang home industry business owner. So that in the future Rengginang home-based business owners will better understand and be able to take advantage of the benefits of digital marketing.